1957
DOI: 10.1177/004051755702700209
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wrinkle-Resistant Finishes for Cotton

Abstract: A brief discussion is given on the mechanism by which wrinkle-resistant properties are imparted to cotton fabrics by the use of urea- and melamine-type resins. A summary of the chemistry of these products is given. The results of an extensive study of the application of urea, modified urea (ethylene urea), melamine. and modified melamine formaldehyde resins using ammonium, alkanolamine, and metallic inorganic salt ac celerators to cotton fabric are presented. The effect of variations in resin concentration, cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1958
1958
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…In addition, the hypothesis has been advanced that the length of this cross link has an effect on the relationship between wrinkle recovery and tensile strength [4] ; that is, the longer the cross link the less loss in strength for an equal ĩ ncrease in wrinkle recovery. The length of this cross link may be a function of (1) the initial mokeu-.…”
Section: Wrinkle Recovermentioning
confidence: 99%
“…In addition, the hypothesis has been advanced that the length of this cross link has an effect on the relationship between wrinkle recovery and tensile strength [4] ; that is, the longer the cross link the less loss in strength for an equal ĩ ncrease in wrinkle recovery. The length of this cross link may be a function of (1) the initial mokeu-.…”
Section: Wrinkle Recovermentioning
confidence: 99%
“…Effect of H)4rolilsis on Wrinkle Recot·c·ryĨ t is well known thaf the CEU resin is susceptible to acid hydrolysis [4). Mazzeno find cho-workers j 11 ] have shown that a solution with a pH below 4 strips most of the CEL.'…”
Section: T Ejnp'raturt O Curingmentioning
confidence: 99%
“…Whenever high crease resistance is obtained by resin treatment, there is obtained concurrently a decrease in the tear, tensile, and abrasion strength of the fabric. As has been pointed out byFoster [5],Cooke and coworkers [3], Stam and coworkers[ 8 ] , and others, the relationship between crease resistance and fabric strength is affected by many factors such as amounts of resin, curing times and temperatures, catalyst concentrations, etc. as well as by the nature of the resin.…”
mentioning
confidence: 94%
“…The curing was held constant at 330° F. for 70 sec., and the resin concentration was held constant at 6.0% solids on the fabric. Cooke and coworkers [3] and Stam and coworkers (8] have already pointed out that better crease resistance-strength relationships can be expected fran the triazine resins than from the cyclic ureu. When the more common types of nitrogenous cra~seproof -ing agents are compared under identical treating conditiona, it is found that the triazones compare favorably with the triazines in crease resistance-strength relationship and are superior to the dimethylol cyclic ureas and dimethylol urea.…”
mentioning
confidence: 99%